THE USE OF HILL CLIMBING ALGORITHM IN GRAPHIC INFORMATION SYSTEM TO FIND THE SHORTEST ROUTE FOR WASTE TRANSPORTATION IN MEDAN DENAI DISTRICT - Putri Harahap, Rahmelia; Syafitri Lubis, Riri; Cipta, Hendra; Syahputri, Linna (Journal of Mathematics and Scientific Computing With Applications, 2025)
Factors causing environmental damage/disaster include internal and external damage. By maximizing the transportation system, we are able to address the social issues optimally so that we provide more positive impacts on public health, environmental health, and urban beauty. Factors related to distribution can make decisions about the routes of transportation. The purpose of this research is to optimize the route of truck transportation using the Hill Climbing Algorithm in the District of Medan Denai from one point to another towards the construction site of the Sentairai. Based on the results of this study, it shows that the route of truck transport to the top with a graphical information system using Ailgorithm Hill Climbing, the route of truck transport to the top with a graphical information system using Ailgorithm Hill Climbing in the District of Medan Aireai with the shortest route for transport to the top is through a route with a total distance of 32.25 km with a travel time of 85 minutess and a total time of 8 hours 20 minutess, namely through: Start Point (Kantor Camat Medan Area) - Pandau Hulu II Village - Kotamatsum II Village - Pasar Merah Timur Village - Kotamatsum III Village - Tegal Sari III Sub-district – Tegal Sari I Sub-district – Sei Rengas Permata Sub-district – Tegal Sari II Sub-district – Sei Rengas II Sub-district – Sukaramai II Sub-district – Sukaramai I Sub-district – Kotamatsum I Sub-district and TPA.